2012
DOI: 10.5089/9781463933807.001
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Inflation in the Euro Area: The Role of Labor and Product Market Institutions

Abstract: While inflation differentials in a monetary union can be benign, reflecting a catch-up process, or an adjustment mechanism to asymmetric shocks or different business cycles, they may also indicate distortions related to inefficiencies in domestic product and labor markets that amplify or make more persistent the impact of shocks on inflation. The paper examines the determinants of inflation differentials in the euro area, with emphasis on the role of country specific labor and product market institutions. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 13 publications
1
3
0
Order By: Relevance
“…These findings support our modeling strategy when neural networks are considered in practical applications, i.e., for forecasting purposes. This is in line with [18,38] who found that multivariate models and more variables can improve inflation forecasts, while it is opposite to findings of [24,28] favoring simpler models. The same conclusion emerges when JNNs are compared with appropriate ARIMA models.…”
Section: Empirical Results and Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…These findings support our modeling strategy when neural networks are considered in practical applications, i.e., for forecasting purposes. This is in line with [18,38] who found that multivariate models and more variables can improve inflation forecasts, while it is opposite to findings of [24,28] favoring simpler models. The same conclusion emerges when JNNs are compared with appropriate ARIMA models.…”
Section: Empirical Results and Discussionsupporting
confidence: 77%
“…The remaining issue is the selection of appropriate exogenous inputs which can be also helpful in reducing the overfitting problem and increasing the forecasting accuracy. In order to include all the aspects of inflation expectations, the characteristics of demand-pull and cost-push inflation are considered, similar to [14,38]. Namely, vector x t in Equation ( 1) is four dimensional, that is, x t = (µ t , ω t , ψ t , δ t ), where µ t represents the monetary expansion rate, ω t is the unit labour cost change, ψ t is the depreciation exchange rate, and δ t is the rate of industrial production change.…”
Section: Modeling Strategy and Datamentioning
confidence: 99%
“…The International Labour Organization (ILO) (2015) highlights that persistently high youth unemployment rates have long-term consequences, for example skills erosion, increase of social exclusion and a higher level of poverty. Furthermore, the experience of unemployment at the beginning of professional life leaves scars, for example in terms of future salary ( Bell and Blanchflower, 2011 ), job and personal satisfaction ( Morsy and Jaumotte, 2012 ) and long-term unemployment ( Arulampalam et al, 2001 ). We demonstrated that psychological capital may facilitate job search as a way to overcome unemployment.…”
Section: Discussionmentioning
confidence: 99%
“…[23] defines financial variables that predict inflation as they reflect current and expected monetary policy responses and measures of real economic activity that predict inflation as they provide information on excess demand. The most commonly used variables are lagged inflation [9,29,31,32]; exchange rates [21,22,30,34]; monetary aggregates [11,27,28]; interest rates [20]; labour market variables, i.e. wages or unit labour costs [16,20]; GDP [9,20,25]; industrial production [7] and fiscal policy variables.…”
Section: Literature Reviewmentioning
confidence: 99%